The effect of stroboscopic effect on human health indicators. (May 2020) - Zhao, X; Hou, D; Lin, Y; Xu, W
The stroboscopic effect from LED light sources can become considerable in working environments. Therefore, this study aims to explore the short-term health effect of a temporal light artefact. The experiment was carried out featuring 10 university students. Three frequencies and three modulation depths were assessed. Psychological reaction was evaluated through subjective scales, while physiological parameters were also collected for mutual validation and analysis. It was found that when the conditions are in the high-risk zone defined by IEEE Standard 1789-2015, subjects considered these conditions to be unacceptable and reported discrete spatial movement and higher visual fatigue levels. Supported by psychological and physiological evidence, it is suggested that such fatigue is caused by a higher chance of flicker. Invisible flicker also significantly affected alpha and beta wave power density, suggesting that a strobe of low frequency could potentially decrease drowsiness and increase cortical arousal. Some limitations to the work performance of this study are also discussed.